Bibliometric Analysis: Research Trends of Guided Inquiry Learning Models in Improving Scientific Attitudes (2015-2024) - Januarni, Baiq Wini (International Journal of Science Education and Science, 2025)
This research analyzes the tren of using the guided inquiry model in improving student’s scientific attitudes in period 2015-2024. Using bibliometric methods with the VOS viewer tool, this research evaluates 200 articles obtained from Google Scholar via Publish or Perish and Dimension AI. The results of the analysis show that the guided inquiry model is an effective approach in scientific learning, because it can increase student’s active involvement, curiosity and problem solving abilities. Publication on this topic have fluctuated, with the highest peak in 2021 (15 publications). This bibliometric analysis provides insight into author productivity, keyword trends, and concept relevance, and shows the potential for further research in this area. The findings are expected to become the basis for developing more innovative and relevant inquiry-based science learning. Keywords: Bibliometric, Guided Inquiry, Scientific Attitudes,